CLASSROOM CIRCLE AS ACTIVITY FOR MAKING EASIER THE DEVELOPMENT OF MORAL JUDGMENT FROM CHILDREN'S EDUCATION - Lepre, Rita Melissa [UNESP]; Oliveira, Bianca de [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2016)
The research presented has the main objective of studying the classroom circle as a permanent activity able to develop the moral judgment of the children, when performed in a planned way, with clear objectives and interventions reflected by the part of the teacher. Through observation, interviews and discussion of moral dilemmas, it was possible verifying that along the classroom circle a range of moral themes arise from the existing conflicts, during or previous to the circle, and it is possible to approach them not only through real episodes, but also, under hypothetical situations from the storytelling or reading of stories and/or dilemmas that contemplate moral themes. Despite these highlighted possibilities, the investigation showed that this space is not used with its full potential. The study at issue corroborates with the idea that the moral development can be, and must be, worked with the children since the kindergarten.
Keywords: Development; Children's Education; Classroom Circle; Moral Judgment